Andrimid, An Antimicrobial Substance Produced by Vibrio Sp. Bacterium Associated with in the Marine Sponge Hyatella Sp. - M. Oclarit , JOSE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The bacterial isolate, M22-1, belonging to the genus Vibrio was obtained from a homogenate of the sponge, Hyatella Sp. The bacterium was cultured in marine agar and was found to produce an antimicrobial compound. The substance was chemically identi- fied as andrimid, a peptide-like antibiotic. The same substance was found in sponge extract, suggesting that the anti-Bacillus activity observed in the homogenate of the sponge body is derived from a product of the associated microorganism